FAKTOR FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN SEKTOR HEALTHCARE - Hidayat, Sarif; Yunus, Taslim Z; Ananto, Tri (Taksasila Edukasi Insani, 2023)
ABSTRACT This study aimed to determine the effect of asset structure, debt management, sales growth, and capital structure on profitability in Healthcare Sector Companies listed on the Indonesia Stock Exchange for the 2017-2021 period.This research is an associative quantitative research, with secondary data. The population is 23 health sub-sector companies listed on the Indonesia Stock Exchange, with a sample of 9 companies obtained by purposive sampling method. The analytical method used is multiple linear regression with panel data using eviews 10.The results showed that asset structure had no significant positive effect on profitability, while debt management had a significant positive effect on profitability. Furthermore, sales growth has a significant negative effect on profitability, while capital structure has no significant negative effect on profitability. Keywords: asset structure, debt management, sales growth, capital structure, profitability